2020
DOI: 10.4103/ijpvm.ijpvm_374_19
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care and weight gain in adolescent compared to adult pregnancy

Abstract: Background: The aim of this study is to compare the antenatal care, body weight, and weight gain in pregnancy between the adolescent and adult pregnancies and, thus, examine the impact of adolescence on the studied parameters. Methods: This prospective study includes 300 pregnant women who were the patients of University Clinical Center Tuzla, Clinic for Gynecology and Obstetrics from January 2011 to December 2014. The women were divided into two groups: an experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…In addition, only one investigation that evaluated the adolescents’ age at the time of pregnancy and their GWG was included in this review; in this study, no association between the adolescents’ age and GWG was reported [ 34 ]. Similar to what has been reported in other studies where adolescents and pregnant adults were compared, gestational weight gain was similar in both groups [ 9 , 11 , 48 , 49 , 50 , 51 , 52 ]. In contrast, there have been studies where it was shown that pregnant adolescents gained more weight compared with pregnant adults [ 43 , 44 , 45 , 53 ].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, only one investigation that evaluated the adolescents’ age at the time of pregnancy and their GWG was included in this review; in this study, no association between the adolescents’ age and GWG was reported [ 34 ]. Similar to what has been reported in other studies where adolescents and pregnant adults were compared, gestational weight gain was similar in both groups [ 9 , 11 , 48 , 49 , 50 , 51 , 52 ]. In contrast, there have been studies where it was shown that pregnant adolescents gained more weight compared with pregnant adults [ 43 , 44 , 45 , 53 ].…”
Section: Discussionsupporting
confidence: 87%